Case report: Primary alveolar soft-part sarcoma of the lung in a child - Xu, Zhufei; Wang, Jinhu; Mao, Junqing; Xu, Dan; Wu, Lei; Zhou, Yunlian; Li, Xuejing; Chen, Zhimin; Wang, Yingshuo (Frontiers in Surgery, 2023)
Alveolar soft-part sarcoma involving the lung is mostly metastatic in nature, while primary alveolar soft-part sarcoma involving the lung occurs more rarely. Herein, we report a rare case of a patient with primary alveolar soft-part sarcoma of the lung, which may represent the earliest onset of this condition reported thus far. In this patient, surgery was performed to excise the lesion to the greatest extent possible, and the combination of surgery with chemoradiotherapy and an antiangiogenic agent may provide an important reference for the development of standard or first-line treatment for such pediatric patients.